2017
DOI: 10.1186/s12934-017-0692-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct hydrogen production from dilute-acid pretreated sugarcane bagasse hydrolysate using the newly isolated Thermoanaerobacterium thermosaccharolyticum MJ1

Abstract: BackgroundEnergy shortage and environmental pollution are two severe global problems, and biological hydrogen production from lignocellulose shows great potential as a promising alternative biofuel to replace the fossil fuels. Currently, most studies on hydrogen production from lignocellulose concentrate on cellulolytic microbe, pretreatment method, process optimization and development of new raw materials. Due to no effective approaches to relieve the inhibiting effect of inhibitors, the acid pretreated ligno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…4 ). In fact, hydrogen may be produced by Coprothermobacter [ 42 44 ], Ruminococcus [ 45 , 46 ], and Thermoanaerobacterium [ 47 , 48 ], and hence any of these organisms may act to syntrophically contribute hydrogen to Methanothermobacter .…”
Section: Discussionmentioning
confidence: 99%
“…4 ). In fact, hydrogen may be produced by Coprothermobacter [ 42 44 ], Ruminococcus [ 45 , 46 ], and Thermoanaerobacterium [ 47 , 48 ], and hence any of these organisms may act to syntrophically contribute hydrogen to Methanothermobacter .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lai et al, reported a hydrogen yield of 1.86 mol/mol consumed sugar using T. aotearoense SCUT27/ ∆ldh from SCB hydrolysate, which was slightly higher than the values obtained in this study (1.68–1.79 mol/mol consumed sugar), but the hydrogen productivity (12.43 mmol/L h) of T. aotearoense SCUT27/ ∆ldh was lower than that of SCUT27/ ∆nfnAB [43]. In addition, the newly isolated strain T. thermosaccharolyticum MJ1 showed a hydrogen yield of 2.52 mol/mol consumed sugar from SCB, but the relatively low hydrogen productivity of 6.55 mmol/L h restricted large-scale production of hydrogen by this strain [21]. The results obtained in the present study indicate that the engineered strain SCUT27/ ∆nfnAB was able to directly use dilute acid-pretreated lignocellulose hydrolysates for hydrogen production with high productivity, yield and substrate use ratio, suggesting that it has great potential to produce hydrogen from nonsterilized lignocellulose hydrolysates.…”
Section: Resultsmentioning
confidence: 99%
“…However, the incineration of lignocellulose resources such as corn stalks and wheat straw is the main disposal approach, which causes serious environment issues (global warming and air pollution) and wastes resources (10.75–11.25 billion tons per year) [20]. As cellulose and hemicellulose in lignocellulose can be hydrolyzed to glucose and xylose, lignocellulosic biomass (e.g., sugarcane bagasse [SCB], corn cob, corn stalk, and wheat straw) has the potential to be used for hydrogen production [15, 21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…In present study, higher bioethanol yield (0.15 kg/kg TSW) and higher bioethanol concentration (87 g/L), this could decrease the cost of distillation process and is a promising way for bioethanol production. Hu and Zhu (2017) reported that pretreated hydrolysate can be used as a substrate to produce biohydrogen. To improve the bioethanol yield from lignocellulose, the bioethanol fermentation potential of pretreated hydrolysate is deserving of further study.…”
Section: Mass Balance Analysismentioning
confidence: 99%